Place the indicated product in the proper location on the grid.
(a - b)(a2 + ab + b2)

Question

Asked 11/20/2014 3:21:30 PM

Updated 11/21/2014 2:42:44 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/21/2014 2:42:44 PM]

s

andrewpallarca|Points 46037|

Question

Asked 11/20/2014 3:21:30 PM

Updated 11/21/2014 2:42:44 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/21/2014 2:42:44 PM]

Rating

8

(a - b)(a^2 + ab + b^2)

= a^3 + a^2b - a^2b+ ab^2 - ab^2 - b^3

= a^3 - b^3

= a^3 + a^2b - a^2b+ ab^2 - ab^2 - b^3

= a^3 - b^3

Added 11/21/2014 2:42:42 PM

This answer has been confirmed as correct and helpful.

Select interior, exterior, or on the circle (x - 5) 2 + (y + 3) 2 = 25 for the following point.
(3, 2) **Weegy:** 2(x - 2) > 3(x - 2); 2x - 4 > 3x - 6; 2x - 3x > -6 + 4; -x > -2; x < 2 (More)

Question

Updated 11/16/2014 9:07:49 PM

1 Answer/Comment

The center of the circle (x - 5)^2 + (y + 3)^2 = 25 is (5, -3), its radius = 5.

The distance between (3, 2) and center (5, -3) is sqrt (2^2 + 5^2) = sqrt 29 = 5.4

5.4 > 5

So the point (3, 2) is exterior the circle (x - 5)^2 + (y + 3)^2 = 25.

The distance between (3, 2) and center (5, -3) is sqrt (2^2 + 5^2) = sqrt 29 = 5.4

5.4 > 5

So the point (3, 2) is exterior the circle (x - 5)^2 + (y + 3)^2 = 25.

Added 11/16/2014 9:07:49 PM

This answer has been confirmed as correct and helpful.

What is a radical expression? **Weegy:** Radicals are the undoing of exponents. ] (More)

In mathematics, a radical expression is defined as any expression containing a radical ( ) symbol.

Question

Updated 11/16/2014 12:01:32 AM

1 Answer/Comment

In mathematics, a radical expression is defined as any expression containing a radical ( ) symbol.

Added 11/16/2014 12:01:32 AM

This answer has been confirmed as correct and helpful.

Factor completely, then place the factors in the proper location on the grid.
x2 - 8x + 16 **Weegy:** 5x^2 ? 8x - 4 = (x - 2)(5x + 2) (More)

Question

Updated 11/18/2014 8:34:24 PM

1 Answer/Comment

x^2 - 8x + 16 = (x - 4)^2

Added 11/18/2014 8:34:24 PM

This answer has been confirmed as correct and helpful.

Place the indicated product in the proper location on the grid.
(w + x)(w + x)

Question

Not Answered

Updated 11/21/2014 2:46:36 PM

1 Answer/Comment

(w + x)(w + x)

= w^2 + wx + wx + x^2

= w^2 + 2wx + x^2

= w^2 + wx + wx + x^2

= w^2 + 2wx + x^2

Added 11/21/2014 2:46:36 PM

This answer has been confirmed as correct and helpful.

Place the indicated product in the proper location on the grid.
(x + 1)(x - 1) **Weegy:** (x + 2)(x - 2) = x^2 - 2x + 2x - 4 = x^2 - 4 (More)

Question

Updated 11/21/2014 2:43:52 PM

1 Answer/Comment

(x + 1)(x - 1)

= x^2 - x + x - 1

= x^2 - 1

= x^2 - x + x - 1

= x^2 - 1

Added 11/21/2014 2:43:52 PM

This answer has been confirmed as correct and helpful.

34,465,578

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 808 [Total 6681] Ratings 19 Comments 618 Invitations 0 Offline

There are no comments.